Gregorio Palamas : Tomo aghioritico : la storia, il testo e la dottrina - Rigo, Antonio (Orientalia Lovaniensia analecta, 2021)
"The volume is dedicated to the Hagiorite tome, one of Gregorios Palamas' most important writings because of its historical relevance and, even more, of its doctrinal and theological significance. This publication outlines the history of the document and the circumstances in which it was drafted by its author and then signed on Mount Athos by a number of representatives of the monastic centre, followed by the critical edition of the Greek text and accompanied by an introduction dedicated to the history of the document and its circulation. Moreover, the volume is enriched by a commentary that explains the role of the tome in the context of Gregorios Palamas' production of the period, as well as how it was composed. Finally, this study clarifies some aspects of Gregorios' biography, and also throws light on contemporary ecclesiastical and monastic circles."--